PHONOPOETICS OF SHUHRAT ARIF’S POETRY (TAMADDUN NURI JURNALI, 2024)
In this article, the linguopoetic features of the works of the famous poet Shuhrat Arif are studied. The article mainly reveals the phonopoetic possibilities of the poet's work, the role of phonetic means in the artistic text is studied.